Immunostimulatory activity and structure-activity relationship of epimedin B from Epimedium brevicornu Maxim. - Gao, Yuan; Shi, Wei; Tu, Can; Li, Peng; Zhao, Guanyu; Xiao, Xiaohe; Wang, Jiabo; Bai, Zhaofang (Frontiers in Pharmacology, 2022)
Epimedii Folium (EF, Epimedium brevicornu Maxim.), a traditional botanical drug, is famous for treating bone fractures, joint diseases, and several chronic illnesses. However, some studies indicated that EF could induce idiosyncratic drug-induced liver injury (IDILI) in the clinic. The NLRP3 inflammasome plays a crucial role in the pathogenesis of various human diseases, including IDILI. In the present study, we showed that epimedin B could specifically facilitate nigericin- or ATP-induced NLRP3 inflammasome activation under synergistic induction of mitochondrial reactive oxygen species. Moreover, epimedin B resulted in activation of Caspase-1 and IL-1β secretion in a lipopolysaccharide (LPS)-mediated susceptibility mouse model. MCC950 pretreatment completely abrogated activation of the NLRP3 inflammasome and prevented liver injury. Importantly, several studies have confirmed that some active constituents of EF could enhance activation of the NLRP3 inflammasome and may be involved in the pathogenesis of EF-IDILI. No reports are available on whether the structure-activity relationship associated with the immunostimulatory activity in EF contributes to the pathogenesis of EF-IDILI. These findings have changed our conventional understanding about the more glycogen, the more immunostimulatory activity.